PATHOGENETIC ASPECTS OF METABOLIC SYNDROME IN WOMEN OF REPRODUCTIVE AGE (A LITERATURE REVIEW) - Nina D. Kastueva; Tatyana D. Tsidaeva; Zalina F. Belikova; Liana V. Maysuradze (Кубанский научный медицинский вестник, 2019)
Aim. The aim of this work was to analyze recently published data on the risk factors and pathogenetic aspects of metabolic syndrome (MS) in women of reproductive age.Materials and methods. This review covers data presented in foreign and Russian literature, which has been published in electronic bibliographic databases Pubmed and the Cochrane Library over the past 10 years. Specifi cally, we carried out an analysis of works containing information on risk factors, pathogenetic aspects and diagnostic criteria of MS in women of reproductive age, as well as on methods currently used for the treatment of this condition.Results. We characterize modern theories that explain mechanisms triggering the development of MS complicated with diabetes 2 type and polycystic ovary syndrome (PCOS). Data on proteomic markers refl ecting the complex pathogenesis of PCOS is generalized, along with their role in the diagnosis and treatment of this disease. The possibility of using these markers for predicting pregnancy outcomes is shown. The importance of regulating metabolic processes for the preparation of women for pregnancy and fertility recovery is emphasized.Conclusion. Hyperandrogenism, insulin resistance, obesity, diabetes 2 type, dyslipidemia, PCOS are shown to be the most signifi cant factors determining pathological changes in fertile age women with metabolic syndrome. The correction of these factors should be included in the course of pregravid preparation for the prevention of adverse pregnancy outcomes.